Salario emocional y su relación con la satisfacción laboral de los colaboradores de una firma consultora - Mayta Chauca, Ruth Elvira (2022)
This investigation was carried out with the purpose of describing the relationship between emotional salary and job satisfaction of the employees of a consultancy firm. The following dimensions are considered for the analysis of the emotional salary: L&D programs, flextime and wellness programs. As for job satisfaction, although there are several factors that have an impact on it, the following are considered for the research: job recognition, working conditions and team relationship. The most appropriate methodological design based on the proposed objectives is a quantitative approach since it attempts to provide solutions to a problem: improving the level of job satisfaction. Additionally, the study will be correlational, given that it is desired to determine the degree of association of the study variables (emotional salary and work satisfaction), and of non-experimental design since the variables will not be manipulated, but rather the relationship at a given moment will be analyzed. Two data collection instruments were applied: surveys and interview. The survey, composed of 40 items, was applied to employees of the consultancy firm, while the interview was conducted with the business partner of the department. After applying the surveys, the information obtained was analyzed by SPSS and it was determined that the emotional salary has a positive and significant relationship with job satisfaction. In addition, it was established that the emotional salary is positively correlated with the dimensions of job satisfaction, so all the proposed hypotheses are verified.